Midline frontal and occipito-temporal activity during error monitoring in dyadic motor interactions. (June 2020) - Moreau, Quentin; Candidi, Matteo; Era, Vanessa; Tieri, Gaetano; Aglioti, Salvatore M.
Abstract: Discrepancies between sensory predictions and action outcome are at the base of error coding. However, these phenomena have mainly been studied focussing on individual performance. Here, we explored EEG responses to motor prediction errors during a human-avatar interaction and show that Theta/Alpha activity of the frontal error-monitoring system works in phase with activity of the occipito-temporal node of the action observation network. Our motor interaction paradigm required healthy individuals to synchronize their reach-to-grasp movements with those of a virtual partner in conditions that did (Interactive) or did not require (Cued) movement prediction and adaptation to the partner's actions. Crucially, in 30% of the trials the virtual partner suddenly and unpredictably changed its movement trajectory thereby violating the human participant's expectation. These changes elicited error-related neuromarkers (ERN/Pe - Theta/Alpha modulations) over fronto-central electrodes during the Interactive condition. Source localization and connectivity analyses showed that the frontal Theta/Alpha activity induced by violations of the expected interactive movements was in phase with occipito-temporal Theta/Alpha activity. These results expand current knowledge about the neural correlates of on-line interpersonal motor interactions linking the frontal error-monitoring system to visual, body motion-related, responses.